(untitled) (Research, Society and Development, 2022)
The study of Agaricomycetes in the Brazilian Pampa Biome is still incipient, but it is very necessary for the valorization and preservation activities in this area. In terms of fungal diversity, it is the least studied Brazilian biome, with only 84 species already described for the site, despite the great diversity of fauna and flora that this biome presents. The objective of this work is to know more about the mycodiversity of this biome, contributing to a better understanding of the distribution and ecology of the Agaricales. The collections were made following the usual methodology for Agaricales (Basidiomycota). Thus, specimens were collected for studies to identification to species level by macro- and microscopic characters. Descriptions of seven species collected in the rural region surrounding the city of São Gabriel, state of Rio Grande do Sul, Brazil are presented, which are cited for the first time for the Pampa Biome, namely: Macrolepiota mastoidea, Protostropharia alcis ssp. austrobrasiliensis, Trogia buccinalis, Crepidotus euterpicola, Entoloma depluens, Lepiota subincarnata and Neopaxillus echinospermus. These new citations reinforce the importance of studies on the biodiversity of the Pampa biome for its preservation.